THE EFFECT OF GIVING RED DRAGON FRUIT JUICE (HYLOCEREUS POLYRHIZUS) ON SPERMATOZOA CONCENTRATION IN WISTAR RATS EXPOSED TO CIGARETTE SMOKE - Ayu Iftitah Salsabiila Harnoko; Lusiana Batubara; Mahayu Dewi Ariani; Donna Hermawati (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2025)
Background : Cigarette smoke contains dangerous chemical components that can produce free radicals and cause oxidative stress, which can reduce sperm quality, including sperm concentration. Rat studies demonstrate that cigarette smoke exposure lowers sperm count by 13–17% and severely affects morphology and motility. Red dragon fruit (Hylocereus polyrhizus) contains vitamin C, vitamin E, beta carotene, lycopene, and flavonoids that function as antioxidants and can counteract the free radicals that enter the body. Purpose : To determine the effect of red dragon juice on the concentration of Wistar rat spermatozoa exposed to cigarette smoke. Method: This study used a post-test only control group design. The total sample was 35 male Wistar rats, divided into 5 groups. Healthy control group is the group without intervention. Negative control group was only exposed to cigarette smoke. Group P1 was exposed to cigarette smoke and given 2 grams/2.5 ml of red dragon fruit juice. Group P2 was exposed to cigarette smoke and given 4 grams/2.5 ml of red dragon fruit juice. Group P3 was exposed to cigarette smoke and given 8 grams/2,5 ml of red dragon fruit juice. Intervention is given for 28 days and on day 29 all rats are terminated and their spermatozoa concentration is checked. Result : The mean concentrations of spermatozoa were: Group K(-) = 42.83; Group K(+) = 31.17; Group P1 = 29.17; Group P2 = 63.33; Group P3 = 72.00. The One Way ANOVA test found a significant difference between the five treatment groups. The Post-Hoc test found significant differences in the K(-) group against K(+), P1, P2, P3. In the K(+) group toward P2 and P3 there was a significant difference. In the P1 to P2, P3 groups, there were significant differences. In the P2 to P3 groups, there was a significant difference. Conclusion : Giving red dragon fruit juice can affect the concentration of spermatozoa in Wistar rats exposed to cigarette smoke.